Power & responsibility : building international order in an era of transnational threats - Jones, Bruce D.; Pascual, Carlos, 1959-; Stedman, Stephen John (Brookings Institution Press, 2009)
"Makes the case for forming new international partnerships and revitalizing instruments of cooperation to address global challenges that post-WWII multilateral security systems cannot. Establishes a new conceptual foundation for international security: 'responsible sovereignty, ' which entails obligations and duties and attitudinal changes toward other states as well one's own"--Provided by publisher